S-glycosylation-based cysteine profiling reveals regulation of glycolysis by itaconate - Qin, Wei; Qin, Ke; Zhang, Yanling; Jia, Wentong; Chen, Ying; Cheng, Bo; Peng, Linghang; Chen, Nan; Liu, Yuan; Zhou, Wen; Wang, Yan-Ling; Chen, Xing; et al. (Nature chemical biology, 2019)
Itaconate has been recently recognized as an anti-inflammatory metabolite involved in the pathogen–macrophage interface. Due to its weak electrophilicity, itaconate could modify cysteines of the protein KEAP1 and glutathione, which contribute to its anti-inflammatory effect. However, the substrates of itaconate modification in macrophages have not been systematically profiled, which largely impedes the understanding of its roles in immune responses. Here, we developed a specific thiol-reactive probe, 1-OH-Az, for quantitative chemoproteomic profiling of cysteine modifications by itaconate, and provided a global portrait of its proteome reactivity. We found that itaconate covalently modifies key glycolytic enzymes and impairs glycolytic flux mainly through inhibition of fructose-bisphosphate aldolase A (ALDOA). Moreover, itaconate attenuates the inflammatory response in stimulated macrophages by impairing the glycolysis. Our study provides a valuable resource of protein targets of itaconate in macrophages and establishes a negative-feedback link between glycolysis and itaconate, elucidating new functional insights for this anti-inflammatory metabolite. Using a thiol-reactive probe, chemoproteomic profiling of cysteine targets of itaconate reveals the covalent modification of glycolytic enzymes, impairing glycolytic flux and contributing to attenuation of the inflammatory response in macrophages.